Impact of Rewards System on Employee Performance: The Case of People's Insurance PLC in Sri Lanka - Francis, S.J.; Hansamalia, H.G.C.; Sirikumar, T.; Ganeshamoorthy, M. (MENTOR The Journal of Business Studies, 2024)
The study provides an extensive review of the impact of various reward mechanisms on employee performance at People's Insurance PLC. Its primary objective is to assess how different components of the reward system such as monetary incentives, recognition programs, and opportunities for career advancement affect employee performance within the organization. The study uses a cross-sectional approach to collect data in the third quarter of 2024, focusing on all 568 employee-level workers at Peoples Insurance PLC in Sri Lanka. Random sampling ensures an unbiased representation, with a calculated sample size of 61 employees selected at a 90% confidence level using purposive sampling techniques. The findings indicate statistically significant positive correlations between various elements of the reward system and employee performance. Salaries, bonuses, and incentives exhibited strong positive correlations, accounting for a considerable portion of the variance in performance outcomes. Recognition initiatives and flexible work arrangements were also found to positively influence performance, albeit to a lesser extent. The study finds that a comprehensive reward system, which includes competitive remuneration, bonuses, incentives, recognition, flexible work arrangements, and healthcare benefits, can significantly enhance employee performance and productivity. It explores theoretical and practical implications, underscoring the importance of monetary and non-monetary rewards in employee ...
Keywords: Rewards System; Employee Performance; Job Satisfaction; Human Resource Management; Career Advancement